PENGGUNAAN BUSINESS MODEL CANVAS SEBAGAI DASAR UNTUK MENCIPTAKAN ALTERNATIF STRATEGI BISNIS DAN KELAYAKAN USAHA - Wisnu Sakti Dewobroto (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
The development of automotive world in this global era has big bump. It is necessary to know that Indonesian market is getting more developing every day. In the future, Indonesian automobile market is expected to be the one of big market. It is estimated that automotive market in Indonesia may absorb 1 million units of automobile every year. 21 DUA SATUMOTOR is located at Jl. Imam Bonjol Raya no 88 Karawaci,Tangerang. 21 DUA SATU MOTOR has purpose to develop business by establishing automobile salon business, considering quietly large opportunity in BSD City Serpong. This research is to firstly, identify outline scheme of company strategy by mapping the automobile salon business in BusinessModel Canvas, secondly, to see business appropriateness from financial area which shall analyze revenue stream area (income) and cost structure (cost) in the established BusinessModel Canvas. Based on Business Model Canvas, it may be concluded that there are 9 important factors in running automobile salon business. Firstly, value of automobile salon better focuses on premium products, facility comfort and quality and guaranteed final result.Secondly, the primary segmentation of automobile salon includes entrepreneurs, private employees or college students ranging from 25-54 year of ages. Third factor is the closeness between the business place and spare part centre in BSD City Serpong. Fourthly, customers arealso interested in membership offer with major facilities of guaranteed automobile salon.Fifthly, to perform all value-oriented activities for potential customers, automobile salon of 21DUA SATU must prioritize key resources on professional human resource and utilization andquality raw materials. In this case, customer-favored mark is 3M. Sixthly, from process side,main activity should focus on automobile salon service and promotion activity. Seventhly, as adrive for improving company performance, partnership is also an important thing. In additionto cooperation with raw material suppliers to get special price and press production cost, banksand credit card providers are also needed to enhance automobile owner interest to try theautomobile salon 21 DUA SATU with discounted facilities. Eighthly, main income ofautomobile salon is the automobile salon package including full total salon package, exteriorsalon package, interior salon package, and wax wash package. Ninthly, necessary costs tocreate value for customers consist of tool cost and its maintenance, promotion cost, labor cost,operational supporting cost and variable cost including water, electricity, phone and rawmaterial of automobile salon. By considering revenue stream and cost structure and analyzingpay back period, proper decision may be made from this automobile salon business of 21 DUASATU. It is assumed that pay back period for this automobile salon of 21 DUA SATU isaveragelycategorized into proper and operable. 3 year. Therefore, this automobile salon business of 21 DUA SATU may be